THE CONCEPT AND EVOLUTION OF INDIA’S SOFT POWER - Dr. Aswathy Satheesh; Smt. Aswathy A.K; Sharon V. Sreeram (IJRDO - Journal of Social Science and Humanities Research, 2026)
The concept of soft power was introduced by Joseph S. Nye Jr. in the late twentieth century as an alternative dimension of power in international relations. Unlike traditional forms of power that rely on military force or economic coercion, soft power emphasizes the ability of a state to influence the behaviour and preferences of others through attraction, persuasion, and legitimacy (Nye, 1990). Nye defines soft power as the ability to achieve desired outcomes through attraction rather than coercion or payment, arguing that culture, political values, and foreign policy constitute its principal sources (Nye, 2004). In this context, power is exercised not through threats or inducements but through the appeal of a country’s ideals, institutions, and cultural achievements. According to Nye (2004), nations that successfully project soft power are able to shape the preferences of other actors and gain international support for their objectives. Soft power therefore involves cultivating a positive national image, promoting attractive values, and generating credibility in the international arena. As global politics becomes increasingly interconnected, the significance of soft power has expanded beyond conventional diplomacy, enabling states to enhance their influence through cultural exchange, public diplomacy, educational outreach, and international cooperation (Nye, 2017). Consequently, soft power has emerged as a crucial component of contemporary foreign policy, complementing rather than replacing traditional hard power resources. In the case of emerging powers such as India, soft power provides an effective means of enhancing global visibility, strengthening diplomatic relations, and promoting national interests through attraction and goodwill rather than coercion.